WATER LEVEL CONTROL SIMULATION ON MINI PLANT WITH FEEDBACK CONTROL STRATEGY USING PROPORTIONAL AND PROPORTIONAL + INTEGRAL CONTROLLERS - Olga, Venettia
Engineering Physics ITB has a mini plant boiler and heat exchanger model BDT921 which can be used as a tool for learning process of system dynamics, instrumentation, and control which consists of 2 main processes, namely water heating in the boiler tank and heat exchanging on the heat exchanger. The hot water that comes out of the boiler tank is considered as system load on the tank and will be used as a heating medium in the heat exchanger. Therefore, the process that occurs in the boiler tank needs to be controlled, so that the heat exchange process in the heat exchanger can be optimal. One of the quantities on the boiler tank that needs to be controlled is the water level (h). Water level control needs to be done precisely in order to obtain a system response that can cope with changes in load and achieve the desired set point value. In this final project research, a feedback control strategy is used using proportional (P) and proportional-integral (PI) controllers. By using the pole placement method, the proportional gain (Kp) and integral gain (Ki) values were 10.256 and 0.513, respectively. Variations in the experiment were to change the level setpoint from 0.5 m to 0.7 m and change the outflow rate from 1 m3 / hour to 4 m3 / hour. Based on the experimental results, the PI controller can give a better response than the P controller because the PI controller can eliminate offsets.